2013
DOI: 10.1080/09593330.2012.715759
|View full text |Cite
|
Sign up to set email alerts
|

Copper, nickel and zinc accumulations in lettuce grown in soil amended with contaminated cattle manure vermicompost after sequential cultivations

Abstract: The Cu, Ni and Zn accumulations in leaves and roots of lettuce (Lactuca sativa L) grown in soil amended with natural and contaminated cattle manure vermicompost were evaluated. The vermicompost residues containing relatively high metal concentrations used in this work were obtained from a previous experiment, in which vermicompost was applied to removing metals from electroplating wastes. Sequential lettuce cultivations were conducted in pots containing the residual substrates from the first cultivation by add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
(24 reference statements)
0
2
0
2
Order By: Relevance
“…S1 and S3). In L. sativa plants, Celik and Kunene [33] also highlighted higher concentrations of Cu and Pb (as well as of Cd, Cr, Fe, Mn and Zn) in roots than in leaves; similarly, Jordão et al [34] found the highest concentrations of Cu and Ni in the belowground organs, attributing this behavior to a protection mechanism. These observations put emphasis on the role that PTE bio-geochemical properties have in explaining element peculiar mobility and transfer into the soil-plant system [30].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…S1 and S3). In L. sativa plants, Celik and Kunene [33] also highlighted higher concentrations of Cu and Pb (as well as of Cd, Cr, Fe, Mn and Zn) in roots than in leaves; similarly, Jordão et al [34] found the highest concentrations of Cu and Ni in the belowground organs, attributing this behavior to a protection mechanism. These observations put emphasis on the role that PTE bio-geochemical properties have in explaining element peculiar mobility and transfer into the soil-plant system [30].…”
Section: Resultsmentioning
confidence: 96%
“…For Cd, the remark is rather worrying, considering its carcinogenicity [36], the For Cu (55.9%), K (7.0%), Mg (16.6%), Na (14.2%) and Pb (28.0%), the organ had a relatively higher contribution in determining their concentrations (Figure 2), with the highest values observed in leaves in the case of Mg and in roots in the case of Cu, K, Na and Pb (Figures S1 and S3). In L. sativa plants, Celik and Kunene [33] also highlighted higher concentrations of Cu and Pb (as well as of Cd, Cr, Fe, Mn and Zn) in roots than in leaves; similarly, Jordão et al [34] found the highest concentrations of Cu and Ni in the belowground organs, attributing this behavior to a protection mechanism. These observations put emphasis on the role that PTE bio-geochemical properties have in explaining element peculiar mobility and transfer into the soil-plant system [30].…”
Section: Resultsmentioning
confidence: 96%
“…Assim, diante do exposto, uma alternativa seria a biofortificação de vegetais cultivados hidroponicamente, como a alface, por exemplo. Como já mencionado, a alface é uma hortaliça amplamente consumida no Brasil, podendo ser cultivada em qualquer época do ano, pois pode ser produzida sob diferentes faixas de temperatura (Jordão et al, 2013). Logo, uma grande quantidade da população poderia ter acesso a maiores quantidades de Se em sua dieta por meio do consumo de alface biofortificada.…”
Section: Determinação Dos Elementos Metálicos Nos Conteúdos Apical Ba...unclassified
“…O e tempo de cultivo da planta. Como as hortaliças estudadas são provenientes do mesmo produtor, os elementos poderiam estar em uma forma em que a alface absorve mais facilmente, podendo acumular maiores quantidades dos elementos em suas folhas(Jordão et al, 2013;Kabata-Pendias, 2001; TACO, 2011).…”
unclassified